2019
DOI: 10.1177/0886260519861657
|View full text |Cite
|
Sign up to set email alerts
|

County Variation in Intimate Partner Homicide: A Comparison of Hispanic and Non-Hispanic Victims

Abstract: Over the past 5 years, intimate partner homicides have increased among Hispanic women, although ethnicity has rarely been brought into macro-level research on intimate partner homicide. These trends have occurred alongside many macro-level changes in the United States. Although both Hispanic and non-Hispanic women are most likely to die at the hands of a partner via a firearm, no study to date has examined the importance of licensed firearm dealer availability in addition to leading macro-level correlates of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 69 publications
(72 reference statements)
1
9
0
Order By: Relevance
“…However, in the present analysis, the presence of DV center shelter services did not significantly relate to FVIPH rates. This finding is contextualized in the mixed shelter–IPH relationship findings in terms of statistical significance and relationship directionality (see Gillespie & Reckdenwald, 2017; Reckdenwald et al, 2018; Reckdenwald & Parker, 2012; Stansfield et al, 2019; Stout, 1989). One explanation could be that availability of services does not equate to access or usage (Reckdenwald & Parker, 2012).…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…However, in the present analysis, the presence of DV center shelter services did not significantly relate to FVIPH rates. This finding is contextualized in the mixed shelter–IPH relationship findings in terms of statistical significance and relationship directionality (see Gillespie & Reckdenwald, 2017; Reckdenwald et al, 2018; Reckdenwald & Parker, 2012; Stansfield et al, 2019; Stout, 1989). One explanation could be that availability of services does not equate to access or usage (Reckdenwald & Parker, 2012).…”
Section: Discussionmentioning
confidence: 90%
“…For example, while not all IPV-related domestic violence firearm policies are associated with lethal IPV (Bridges et al, 2008), restraining order firearm laws (in their various forms) generally are associated with decreased lethal IPV rates (see Díez et al, 2017; Vigdor & Mercy, 2006; Zeoli et al, 2018; Zeoli & Webster, 2010). Stansfield et al (2019) and Stout (1989) found that policies, laws, and legislation generally exacted a protective association against lethal IPV. The ordinances found in the present research may have been too specific in scope to have a measurable impact.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations